2018
DOI: 10.1590/1984-9250875
|View full text |Cite
|
Sign up to set email alerts
|

The myth of racial democracy in the labour market: a critical analysis of the participation of afro-descendants in brazilian companies

Abstract: This research sought to identify the participation of different races in organizations and to investigate the opportunities for black people, in terms of employability and professional growth, in Brazil. To meet this objective, documentary research was undertaken with 117 companies, which are among the 500 largest in Brazil. The results indicated that racial democracy is a myth in our society, hence the need to move forward with social policies that minimize inequalities between white and black people in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
1
0
2
Order By: Relevance
“…It is understood that, based on the Mourean perspective, it is possible to expand analysis regarding how organizations constitute decisive spaces for the production and reproduction of racial inequalities. It is observed that, in the realm of work, race-related issues are often addressed under the umbrella of diversity (Machado, Bazanini, & Mantovani, 2018). Moura can help us reflect on how the instruments discussed within this "paradigm" are insufficientif not impediments -for a mass upward mobility of oppressed groups.…”
Section: Discussion and Final Considerationsmentioning
confidence: 99%
“…It is understood that, based on the Mourean perspective, it is possible to expand analysis regarding how organizations constitute decisive spaces for the production and reproduction of racial inequalities. It is observed that, in the realm of work, race-related issues are often addressed under the umbrella of diversity (Machado, Bazanini, & Mantovani, 2018). Moura can help us reflect on how the instruments discussed within this "paradigm" are insufficientif not impediments -for a mass upward mobility of oppressed groups.…”
Section: Discussion and Final Considerationsmentioning
confidence: 99%
“…Isso se evidencia em pesquisa que apresenta a democracia racial como um mito na sociedade brasileira, pois os cargos empresariais mais elevados têm predominância branca. Em contrapartida, os cargos mais baixos da pirâmide organizacional dessas empresas são ocupados, em grande maioria, por pessoas negras (Machado Júnior et al, 2018).…”
Section: Discussionunclassified
“…Entende-se que, com base no ponto de vista moureano, seja possível expandir análises a respeito de como as organizações constituem espaços decisivos de produção e reprodução de desigualdades raciais. Observa-se que, na esfera do trabalho, questões relacionadas a raça costumam ser tratadas sob o guarda-chuva da diversidade (Machado, Bazanini, & Mantovani, 2018). Moura pode nos ajudar a refletir como os instrumentos discutidos no interior desse "paradigma" são insuficientes -quando não impeditivos -para uma ascensão vertical em massa das camadas oprimidas.…”
Section: -12unclassified